2022
DOI: 10.1099/ijsem.0.005237
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus huangpiensis sp. nov. and Lactobacillus laiwuensis sp. nov., isolated from the gut of honeybee (Apis mellifera)

Abstract: Four Gram-stain-positive bacterial strains were isolated from the gut of honeybee (Apis mellifera) in China. These strains were characterized using a polyphasic taxonomic approach. The data demonstrated that three of the four strains represented two novel species of the genus Lactobacillus , strains F306-1T and F551-2T were designated as the type strains. Results of 16S rRNA gene sequence analysis indicated that strains F306… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The same findings were reported for different or identical phylotypes of the genus Lactobacillus originating from honeybees guts and their food [ 58 , 64 , 65 ]. Recently, three and two species belonging to Apilacobacillus and Lactobacillus , respectively, were described as novel and hosting the Apis mellifera gut [ 10 , 66 , 67 ]. Lactobacillus kimbladii and Lactobacillus kullabergensis , belonging to the Firm-5 clade, were commonly identified as the most numerically abundant phylotype in honey bee guts [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same findings were reported for different or identical phylotypes of the genus Lactobacillus originating from honeybees guts and their food [ 58 , 64 , 65 ]. Recently, three and two species belonging to Apilacobacillus and Lactobacillus , respectively, were described as novel and hosting the Apis mellifera gut [ 10 , 66 , 67 ]. Lactobacillus kimbladii and Lactobacillus kullabergensis , belonging to the Firm-5 clade, were commonly identified as the most numerically abundant phylotype in honey bee guts [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic characteristics were investigated as described previously [4, 33]. Resistance to antibiotics was investigated by adding them in mMRS solid medium [34].…”
Section: Full-textmentioning
confidence: 99%
“…High completeness (85.2-99.4 %) and low contamination (0.6-3.1 %) showed that the genomes used in this study were of high quality (Table S5). Phenotypic characteristics were investigated as described previously [4,33]. Resistance to antibiotics was investigated by adding them in mMRS solid medium [34].…”
mentioning
confidence: 99%
“…In the genus Lactobacillus, Lactobacillus huangpiensis, Lactobacillus laiwuensis, Lactobacillus helsingborgensis, Lactobacillus melliventris, Lactobacillus kimbladii, Lactobacillus kullabergensis, Lactobacillus apis, Lactobacillus panisapium and Lactobacillus bombicola are associated with bees (Table S1, available in the online version of this article) [1][2][3][4][5], and they form a small phylogenetic branch (L. melliventris clade) [1,6]. All of them are members of Firm5 in honeybee gut microbiota [7].…”
mentioning
confidence: 99%
“…Phenotypic features were investigated as described previously [1,8]. Resistance to antibiotics was investigated at four concentrations (5, 50, 100 and 300 µg ml -1 ) by adding antibiotics to mMRS solid medium [29].…”
mentioning
confidence: 99%